IDENTIFIKASI GAYA PILAR DAN PELENGKUNG ISTANA MAIMUN - Lolita Refani Lumban-Tobing (Balai Arkeologi Sumatera Utara, 2019)
Maimun Palace is one of cultural heritage buildings in Medan that is interesting to study, because this building showed a mix style between traditional Malay and foreign architectural style. This research focuses on building as a representation of a cultural process, where the study is centered on the influence of foreign culture on the pillars and arches of the Maimun palace. This research use descriptive method and continued with contextual analysis. The conclusion of this study is that the pillars and arches of the Maimun Palace gained influence from the Moorish architectural style originating from the Ummayah dynasty in Spain (Andalusia) and also traditional Malay, but this influence was not a direct influence, because of the time context between the end of the Ummayah dynasty and the construction of the Maimun Palace it is not in accordance with. The influence of this style is assumed to be arised due to the use of European architect in the construction process.